2022
DOI: 10.3390/nu14020323
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density Changes in Long-Term Kidney Transplant Recipients: A Real-Life Cohort Study of Native Vitamin D Supplementation

Abstract: Vitamin D insufficiency has been associated with reduced bone mineral density (BMD) in kidney transplant patients (KTRs). However, the efficacy of vitamin D supplementation on BMD remains poorly defined, especially for long-term KTRs. We aimed to investigate the effect of native vitamin D supplementation on the BMD of KTRs during a 2-year follow-up. Demographic, clinical, and laboratory data were collected. BMD was evaluated with standard DEXA that was performed at baseline (before vitamin D supplementation) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…With regard to bisphosphonates, most of the relevant studies (including meta-analyses) have found that the use of bisphosphonates by kidney transplant recipients is associated with a BMD gain [ 42–44 ] but not with a lower risk of incident fractures [ 42–44 ]. Concerning vitamin D, a recent study did not find an increase in BMD after 2 years of vitamin D supplementation [ 45 ]; this is also consistent with the literature data [ 46 ]. On the same lines, there is no evidence to suggest that vitamin D supplementation reduces the fracture risk [ 46 ].…”
Section: Discussionsupporting
confidence: 90%
“…With regard to bisphosphonates, most of the relevant studies (including meta-analyses) have found that the use of bisphosphonates by kidney transplant recipients is associated with a BMD gain [ 42–44 ] but not with a lower risk of incident fractures [ 42–44 ]. Concerning vitamin D, a recent study did not find an increase in BMD after 2 years of vitamin D supplementation [ 45 ]; this is also consistent with the literature data [ 46 ]. On the same lines, there is no evidence to suggest that vitamin D supplementation reduces the fracture risk [ 46 ].…”
Section: Discussionsupporting
confidence: 90%
“…On the contrary, a recent analysis of 259 patients with a mean PTH of 129 pg/ml at 9 months after transplantation revealed a relationship between the duration of steroid use but not PTH level with the changes in the BMD after 2 years [20]. Similarly, among patients with a transplant vintage of 6 years and an average PTH of 83 pg/ml, no relationship between PTH level with WHO criteria for osteopenia and osteoporosis at the lumbar spine and the femoral neck was observed [21 ▪▪ ]. A prospective observational study of 518 de-novo kidney transplant recipients revealed that PTH at the time of transplantation was not predictive of incident fracture after 5 years [22].…”
Section: Discussionmentioning
confidence: 96%
“…The current findings do not support the beneficial effects of high-dose vitamin D supplements on bone health, which may even confer a substantial reduction in BMD, risk of falls, fractures or a small increase in myocardial infarction 36. Excluding people with normal renal function, in kidney transplant recipients, a recent study showed that supplementation with inactive vitamin D did not modify the urinary calcium nor the BMD, Z-score or T-score at lumbar bodies and the femoral neck in kidney transplant recipients 37. According to the current available evidence, the benefits of vitamin D supplementation in humans are more biased towards a ‘U-shaped’ association.…”
Section: Discussionmentioning
confidence: 99%